DEVELOPMENT OF COWPEA (Vigna unguiculata) SPROUTS FLOUR AS A FUNCTIONAL CEREAL HIGH IN DIETARY FIBER AND ANTIOXIDANT POTENTIAL - Setyaningrum Ariviani; Nurul Hidayati Sholihin; Galih Poetri Nastiti (Universitas Sebelas Maret (UNS), 2021)
The average consumption of dietary fiber in Indonesian is still below the recommended daily intake. Low dietary fiber intake has an impact on the development of degenerative diseases and metabolic syndrome. One of the risk factors for the occurrence of the disease is oxidative stress. The most effective strategy to overcome oxidative stress is through dietary antioxidants intake. Cowpea is proven to be rich in bioactive compounds such as flavonoids, dietary fiber as well as antioxidants, and these compounds have been successfully increased by germination. This study aims to develop cowpea sprouts flour as a functional cereal high in dietary fiber and antioxidants. The cereal was prepared by the best formula based on two steps of sensory analysis. The first one, the sensory analysis conducted to select the formula based on the best sensory quality of the cereal made by the various proportions of cowpea flour (%b/b) (80, 85, 90, 95, 100). The selected formula was further used to prepare the cereal with different flavoring agents (5% b/b) (ginger, cinnamon, and ginger-cinnamon) to find the best formula based on the preference level. The cereals were further analyzed to determine the sensory quality compared to the commercial cereal, the dietary fiber content which includes the total, soluble, and insoluble dietary fibers, as well as the antioxidant potential with the total phenolic content (TPC) evaluation. Formula with 80%(b/b) cowpea flour and 5% (b/b) ginger as flavoring agents produce cereal with the highest preference level and stated as the best formula. The cowpea sprouts cereal exhibited a significantly higher quality of aroma, texture, and overall than the commercial ones. The cereal also showed the highest levels of total, soluble and insoluble dietary fiber as well as the TPC. These results have significant implications on the development of functional cereal using locally legumes sprouts flour.